2021
DOI: 10.3389/fphys.2021.667330
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity Measurements and Metabolic Syndrome Are Linked Through Circulating Neuregulin 4 and Adipsin Levels in Obese Adults

Abstract: BackgroundAdiposity and adipokines are associated with metabolic disorders, but little is known regarding that whether adiposity measurements link metabolic syndrome (MetS) through circulating neuregulin 4 (Nrg4) and adipsin levels.Materials and MethodsA total of 1212 subjects with a waist circumference greater than 90 cm for men or 80 cm for women were enrolled from a Chinese community. Circulating Nrg4 and adipsin levels were measured using commercial kits. Mediation analyses of circulating Nrg4 and adipsin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…Elevated levels of adipsin in CG confirm previous studies on the level of adipsin in humans with the normal level of adipose tissue ( Napolitano et al., 1994 ). This observation also confirms the study that indicated a direct relationship between obesity, fat tissue, and adipsin ( Guo et al., 2021 ; Vasilenko et al, 2017 ). Since MetS can lead to T2DM, this study partially undermines previously reported results indicating depletion of adipsin levels in T2DM patients ( Zhou et al, 2018 ).…”
Section: Methodssupporting
confidence: 91%
“…Elevated levels of adipsin in CG confirm previous studies on the level of adipsin in humans with the normal level of adipose tissue ( Napolitano et al., 1994 ). This observation also confirms the study that indicated a direct relationship between obesity, fat tissue, and adipsin ( Guo et al., 2021 ; Vasilenko et al, 2017 ). Since MetS can lead to T2DM, this study partially undermines previously reported results indicating depletion of adipsin levels in T2DM patients ( Zhou et al, 2018 ).…”
Section: Methodssupporting
confidence: 91%
“…Other adipokines whose levels are higher in obese subjects compared to normal-weight individuals include resistin [ 71 , 72 ], visfatin [ 73 , 74 ], apelin [ 30 , 75 , 76 ], the fatty acid binding protein specific for adipocytes (FABP4) [ 77 , 78 ], adipsin [ 79 , 80 ], and irisin [ 81 , 82 ].…”
Section: Dysfunctional Adipose Tissue In Obesity: Alteration Of the A...mentioning
confidence: 99%
“…Adipsin/complement factor D, a member of the serine protease family, controls the alternative complement pathway and was one of the first adipokines described in 3T3 adipocytes [ 111 ]. Adipsin levels were found to be increased in obese patients compared to non-obese subjects [ 79 , 80 ], while they were reduced in patients with T2D compared to non-diabetic controls [ 112 , 113 ]. In addition, no changes in adipsin levels were found in obese subjects without diabetes compared to obese patients with T2D [ 70 ].…”
Section: Dysfunctional Adipose Tissue In Obesity: Alteration Of the A...mentioning
confidence: 99%
“…These results demonstrated that circulating Nrg4 levels were similarly reduced in obesity, consistent with findings in adipose tissue ( Comas et al, 2019 ; Wang et al, 2020 ), suggesting that Nrg4 deficiency may be an important feature of obesity. Another recent study including adults with obesity of the same community origin further identified that both circulating Nrg4 and adipsin levels were significantly associated with waist circumference, visceral fat, and MetS, providing additional clinical evidence for the association of Nrg4 with obesity ( Guo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 93%